(untitled) (Philological Studies, 2019)
The article deals with the reflection of Horace’s idea of moderate and just life in Gogol’s “Taras Bulba”. It is proved that Gogol has learned not only the ethics of Horace, but his poetics, his notion of work and rest. Motives of Horace were used by Gogol to idealize the past and to clarify the importance of different forms of justice. Gogol’s romantic conservatism is only a form of “justice”, polemically sharpened, and not the final position.